2016
DOI: 10.1101/094383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic flexibility in striatal-cortical circuits supports reinforcement learning

Abstract: Complex learned behaviors must involve the integrated action of distributed brain circuits. While the contributions of individual regions to learning have been extensively investigated, understanding how distributed brain networks orchestrate their activity over the course of learning remains elusive. To address this gap, we used fMRI combined with tools from dynamic network neuroscience to obtain time--resolved descriptions of network coordination during reinforcement learning. We found that learning to assoc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 68 publications
(73 reference statements)
7
69
0
Order By: Relevance
“…Greater switching behaviour of the subgraph illustrates increasing flexibility of the interaction between functional systems after musical training. Noteworthy, the flexible interaction has been shown between functional systems during executive cognition [4], reinforcement learning [39], and musical training [25]. In the current study, flexible interaction was found between the primary functional systems, as well as the higherorder cognitive related systems-cingulo-opercular task control and salience systems.…”
Section: Discussionsupporting
confidence: 55%
“…Greater switching behaviour of the subgraph illustrates increasing flexibility of the interaction between functional systems after musical training. Noteworthy, the flexible interaction has been shown between functional systems during executive cognition [4], reinforcement learning [39], and musical training [25]. In the current study, flexible interaction was found between the primary functional systems, as well as the higherorder cognitive related systems-cingulo-opercular task control and salience systems.…”
Section: Discussionsupporting
confidence: 55%
“…(c) Whole-brain thresholded activation maps for CPP and RU from McGuire et. al(2014) and whole-brain maps for edge strength of subgraph 4 in the current study. Optimal parameters for nonnegative matrix factorization.…”
mentioning
confidence: 54%
“…(b) Relationship between the activation for RU and the edge strength of subgraph 4. We observed a significant positive correlation between the z statistic for RU from McGuire et al(2014) and the edge strength across nodes in subgraph 4. The red line represents the regression line and the shaded area represents the 95% confidence interval.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Network flexibility demonstrates low values in healthy controls, intermediate values in siblings of people with schizophrenia, and high values in people with schizophrenia [Braun et al, 2016]. Finally, individual differences in network flexibility have been shown to correlate with individual differences in performance on tasks requiring executive function including motor learning [Bassett et al, 2011] and reinforcement learning [Gerraty et al, 2016]. Yet, despite the success of dynamic network methods generally as well as the neurophysiological relevance of network flexibility for executive function specifically, much work still remains to devise metrics of reconfiguration that best capture neurophysiological processes.…”
Section: Introductionmentioning
confidence: 98%